Innovative, Ideal, And Fun Classroom Management To Improve Reading Literacy Of Madrasah Ibtidaiyah Students - Wa Mirna; Siti Nurjanah (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to describe: 1) innovative, ideal, and fun classroom management plans to improve students' reading literacy in class IIB at MIN 2 Ambon, 2) The teacher's role in classroom management is innovative, ideal, and fun to improve students' reading literacy in class. IIB at MIN 2 Ambon, the role of the principal in supervising the management of innovative, ideal, and fun classrooms to improve students' reading literacy in class IIB at MIN 2 Ambon, and 4) supporting and inhibiting factors for innovative, ideal, and fun classroom management to improve reading literacy of students in class IIB at MIN 2 Ambon. This type of research is a qualitative research with a phenomenological research design. Data collection techniques using interviews, observation, and documentation. The results showed that in MIN 2 Ambon, innovative, ideal, and fun classroom management had been carried out well to improve students' reading literacy in class IIB at MIN 2 Ambon. Classroom management planning is carried out by arranging facilities, teaching management and student arrangements. The teacher's role in learning is to be a class manager or teaching manager, the teacher also acts as a facilitator, motivator, demonstrator, mediator, and evaluator. The principal's role is to monitor teacher performance continuously in literacy activities and programs in schools. The supporting factors and inhibiting factors for classroom management are the physical environment, social emotional condition and organization at the MIN 2 Ambon school